2020
DOI: 10.3390/ijerph17239126
|View full text |Cite
|
Sign up to set email alerts
|

Groundwater Chemical Characteristics and Controlling Factors in a Region of Northern China with Intensive Human Activity

Abstract: The identification of groundwater chemical characteristics and the controlling factors is of major concern in water environment studies. In this study, we identified the groundwater chemical characteristics, evolution laws and main control factors in a region severely affected by human activities using hydrochemical and multivariate statistical techniques. The results showed that the concentrations of NO3− and TH were the primary pollution factors in the region with intensive human activity because of high con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The correlations between the chemical components could reflect the source of each parameter [ 7 , 28 ]. As it can be seen from Figure 8 , there were significant positive correlations between TH, TDS, Na + , Ca 2+ , Mg 2+ , Cl − , HCO 3 − , and SO 4 2− .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlations between the chemical components could reflect the source of each parameter [ 7 , 28 ]. As it can be seen from Figure 8 , there were significant positive correlations between TH, TDS, Na + , Ca 2+ , Mg 2+ , Cl − , HCO 3 − , and SO 4 2− .…”
Section: Resultsmentioning
confidence: 99%
“…Anthropogenic activity is also a major factor controlling the hydrochemical characteristics of groundwater. Previous studies have found that domestic sewage, industrial wastewater, and chemical fertilizers are important factors controlling the hydrochemical characteristics of groundwater in areas where human activity is intense, such as alluvial-pluvial fan zones and urban areas [ 4 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the wastewater contains dozens of harmful substances such as formaldehyde, acetone, chloride, preservatives, limestone, etc. These substances make the groundwater contain a large number of anions, such as , , , and cations, such as , which make the groundwater acidic or alkaline [ 22 ] and harmful to human health, crop production, animal husbandry, and so on [ 23 ]. Hence, the wastewater should be purified before it is discharged into the outside world.…”
Section: Case Studymentioning
confidence: 99%
“…Compared with surface water, groundwater is less disturbed by external factors and can ensure a continuous and stable supply of good-quality fresh water over long time periods ( Aeschbach-Hertig and Gleeson, 2012 ; Griebler and Avramov, 2015 ). However, human reliance on groundwater is increasing, and human activities are gradually affecting the quality of groundwater and ecological balance ( Danielopol et al, 2003 ; Gerth and Förstner, 2004 ; Li et al, 2018 ; Ren and Zhang, 2020 ; Zhou B. et al, 2021 ; Lan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%